Assessing Unwanted Variations in Rheumatology Clinic Previsit Rooming. Issue 3 (April 2019) - Ramly, Edmond; Stroik, Brad; Lauver, Diane R.; Johnson, Heather M.; McBride, Patrick; Steffen Lewicki, Kristin; Arnason, Jon; Bartels, Christie M.
Abstract : Background: Rheumatologists face time pressures similar to primary care but have not generally benefitted from optimized team-based rooming during the time from the waiting room until the rheumatologist enters the room. Objective: The aim of this study was to assess current capacity for population management in rheumatology clinics; we aimed to measure the tasks performed by rheumatology clinic staff (medical assistants or nurses) during rooming. Methods: We performed a cross-sectional time-study and work-system analysis to measure rooming workflows at 3 rheumatology clinics in an academic multispecialty practice during 2014–2015. We calculated descriptive statistics and compared frequencies and durations using Fisher exact test and analysis of variance. Results: Observing 190 rheumatology clinic previsit rooming sequences (1419 minutes), we found many significant variations. Total rooming duration varied by clinic (median, 6.75–8.25 minutes; p < 0.001). Vital sign measurement and medication reconciliation accounted for more than half of rooming duration. Among 3 clinics, two of 15 tasks varied significantly in duration, and 9 varied in frequency. Findings led clinic leaders to modify policies and procedures regarding 6 high-variation tasks streamlining assessment of weight, height, pain scores, tobacco use, disease activity, and refill needs. Conclusions: Assessing rheumatology rooming tasks identified key opportunities to improve quality and efficiency without burdening providers. This project demonstrated user-friendly methods to identify opportunities to standardize rooming and support data-driven decisions regarding rheumatology clinic practice changes to improve population management in rheumatology. Abstract : Supplemental digital content is available in the text.